Subditine, a new monoterpenoid indole alkaloid from bark of nauclea subdita (Korth.) steud. induces apoptosis in human prostate cancer cells. - Leong, K.H. (Public Library of Science, 2014)
In this study, a new apoptotic monoterpenoid indole alkaloid, subditine (1), and four known compounds were isolated from the bark of Nauclea subdita. Complete 1H- and 13C- NMR data of the new compound were reported. The structures of isolated compounds were elucidated with various spectroscopic methods such as 1D- and 2D- NMR, IR, UV and LCMS. All five compounds were screened for cytotoxic activities on LNCaP and PC-3 human prostate cancer cell-lines. Among the five compounds, the new alkaloid, subditine (1), demonstrated the most potent cell growth inhibition activity and selective against LNCaP with an IC50 of 12.24±0.19 µM and PC-3 with an IC50 of 13.97±0.32 µM, compared to RWPE human normal epithelial cell line (IC50 = 30.48±0.08 µM). Subditine (1) treatment induced apoptosis in LNCaP and PC-3 as evidenced by increased cell permeability, disruption of cytoskeletal structures and increased nuclear fragmentation. In addition, subditine (1) enhanced intracellular reactive oxygen species (ROS) production, as reflected by increased expression of glutathione reductase (GR) to scavenge damaging free radicals in both prostate cancer cell-lines. Excessive ROS could lead to disruption of mitochondrial membrane potential (MMP), release of cytochrome c and subsequent caspase 9, 3/7 activation. Further Western blot analyses showed subditine (1) induced down-regulation of Bcl-2 and Bcl-xl expression, whereas p53 was up-regulated in LNCaP (p53-wild-type), but not in PC-3 (p53-null). Overall, our data demonstrated that the new compound subditine (1) exerts anti-proliferative effect on LNCaP and PC-3 human prostate cancer cells through induction of apoptosis.